Penyusunan Sistem Informasi Geografis Infrastruktur Transportasi Kabupaten Kapuas Hulu Berbasis WEB - Juniardi, Ferry; Azwansyah, Heri (ELKHA : Jurnal Teknik Elektro, 2014)
Abstract The availability of adequate transportation infrastructure data is something that is very important in the development of transport infrastructure policy formulation. The study is to construct a system of geographic information Kapuas Hulu transport infrastructure built web-based. This study requires transportation infrastructure data obtained from relevant agencies, field surveys and various reference sources. The study provides a geographic information system of transportation infrastructure Kapuas Hulu web-based GIS. The system can handle the data input process and the search process data and perform spatial functions properly. The system can also show the spread of transport which is described in the form of maps so that users know more clearly the existing transportation in Kapuas Hulu. Keywords Transport infrastructure, GIS, Web